Quality of life in adolescents with primary headaches - Naomi Riahta; Muhammad Ali; Bistok Saing; Yazid Dimyati; Johannes Saing (Indonesian Pediatric Society, 2013)
Background Headaches are common problems in adults,adolescents, and children. Headaches impact a child's life, theirfamily life, and even society. An assessment of quality of life inadolescents with primary headaches may help to determine actionsnecessary to improve the quality of life of these patients.Objective To assess the quality oflife of adolescents with primaryheadach es compared to healthy adolescents.Methods We conducted a cross-sectional study in December2009 on adolescents aged 13 to 18 years. The headache groupconsisted of children with primary headaches according to theInternational Classification of Headache Disarders and the controlgroup consisted of healthy adolescents. Subjects were selected byconsecutive sampling, with 75 subjects in each group. Subjectsfilled the Pediatric Quality of Life Inventary version 4.0 (PedsQL4.0) questionnaire.Results The mean PedsQL total score was significantly lowerin the headache group than in the contra 1 group [ l 7 5. 7 vs.392.2, respectively, (95%CI of differences -28.l to -219.3, P =0.001)]. However, out of23 items in the questionnaire, 9 werenot significantly different between the headache and controlgroups.Conclusions Primary headaches in adolescents is associatedwith lower quality of life. Most quality of life domains scoresare significantly lower in adolescents with primary headachescompared to those without primary headaches.